2016
DOI: 10.1118/1.4950873
|View full text |Cite
|
Sign up to set email alerts
|

Performance characteristics of dedicated molecular breast imaging systems at low doses

Abstract: The CZT system demonstrated better uniformity, count sensitivity, spatial resolution, energy resolution, and lesion detection in phantom and patient studies compared to the NaI system. At administered doses of 150-300 MBq Tc-99m sestamibi, patient results obtained with CZT systems may not be directly translatable to NaI systems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
38
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(38 citation statements)
references
References 27 publications
0
38
0
Order By: Relevance
“…Molecular breast imaging (MBI) uses a small dual‐headed semiconductor‐based gamma camera in a mammographic configuration to obtain high‐resolution functional images of 99m Tc‐sestamibi uptake in the breast . Modern MBI systems use pixelated solid‐state cadmium zinc telluride (CZT) detector array optimized for near‐field imaging with collimator septa matched to pixel spacing yielding superior spatial resolution and sensitivity compared with conventional gamma cameras . The MBI examination typically involves an intravenous administration of 99m Tc‐sestamibi, with imaging commencing roughly 5 min after injection.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Molecular breast imaging (MBI) uses a small dual‐headed semiconductor‐based gamma camera in a mammographic configuration to obtain high‐resolution functional images of 99m Tc‐sestamibi uptake in the breast . Modern MBI systems use pixelated solid‐state cadmium zinc telluride (CZT) detector array optimized for near‐field imaging with collimator septa matched to pixel spacing yielding superior spatial resolution and sensitivity compared with conventional gamma cameras . The MBI examination typically involves an intravenous administration of 99m Tc‐sestamibi, with imaging commencing roughly 5 min after injection.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] Modern MBI systems use pixelated solid-state cadmium zinc telluride (CZT) detector array optimized for near-field imaging with collimator septa matched to pixel spacing yielding superior spatial resolution and sensitivity compared with conventional gamma cameras. 4,5 The MBI examination typically involves an intravenous administration of 99m Tc-sestamibi, with imaging commencing roughly 5 min after injection. The patient's breast is placed directly onto one detector head, while the other detector is lowered until light compression (~15 lbs.)…”
Section: Introductionmentioning
confidence: 99%
“…Over the last 20 years, research has demonstrated the value of compact high resolution gamma cameras for dedicated nuclear medicine breast imaging as a means of mitigating the lack of resolution and sensitivity of standard large cameras 15 . Three main types of gamma cameras are currently being implemented: scintillation cameras with position sensitive photomultiplier tubes (PSPMTs) for PET and SPECT, scintillation cameras using silicon photomultipliers (SiPMs) for PET, and solid state direct-conversion semiconductor cameras for PET and SPECT.…”
Section: Introductionmentioning
confidence: 99%
“…The most commonly used solid-state semiconductor is cadmium zinc telluride (CZT). CZT arrays exhibit good gamma ray detection efficiency and have been shown to have very good energy resolution 5,1012 , but suffer from low energy tailing due to hole trapping. CZT systems are currently available from a small number of sources at a great cost for low-defect samples.…”
Section: Introductionmentioning
confidence: 99%
“…Some dedicated MBI detectors comprise pixelated arrays of sodium iodide coupled to position-sensitive photomultiplier tubes (also known as breast-specific g-imaging (2)). Other detector configurations include a multicrystal array of cesium iodide coupled to solid-state silicon photodiodes (3) and a completely solid-state detector that uses cadmium-zinc-telluride (2). Collimators for MBI systems can vary in design.…”
mentioning
confidence: 99%